Arctic regions and British America : containing all the discoveries in the Arctic seas up to 1853 - Bartholomew, John, 1831-1893. (Cartographer)
Map of British America focusing on water trails and portages to get across the country and to the Arctic. Also includes (primarily anglo) place names, dates and names of expeditions and their captains, and lakes and rivers. [Originally published : Black's atlas of North America 1856] XLV-I. Includes inset maps of searching expeditions under the command of cap. Austin and cap. Penny 1851, and the site of Sir J. Frankin's Winter quarters Map coloured to show the outline of British territories and the routes of ship voyages or portages from the Atlantic across the country and into the North. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ . Edinburgh : Adam and Charles Black, [1859-1865]